Accelerated Polypeptide Synthesis via N‐Carboxyanhydride Ring Opening Polymerization in Continuous Flow. Issue 18 (20th July 2020) - Vrijsen, Jeroen Hendrik; Rasines Mazo, Alicia; Junkers, Tanja; Qiao, Greg Guanghua
Abstract : In nature, polypeptide‐based materials are ubiquitous, yet their synthetic production is hampered by high cost, limited scalability, and often stringent reaction conditions. Herein an elegant approach is presented for N ‐carboxyanhydride ring opening polymerization (NCA ROP) of Nε ‐benzyloxycarbonyl‐l ‐lysine (ZLL) and γ‐benzyl‐l ‐glutamate (BLG) NCA in continuous flow. The polymerization is initiated by primary amine initiators using N, N‐ dimethylformamide (DMF) as solvent. Carrying out the reaction in a silicon microflow reactor speeds up the rate of ROP (92% conversion in 40 min in flow as opposed to 6 h in batch) due to highly efficient permeation of CO2 through the reactor tubing. The polymerization strategy provides a facile, scale‐up friendly alternative to traditional batch mode polymerization and has the capability of streamlining NCA ROP. Abstract : N ‐carboxyanhydride ring opening polymerization in traditional systems often suffers from slow polymerization. Substantial acceleration is observed in this work by performing the polymerization in a silicon microflow reactor due to more efficient removal of the CO2 byproduct. This continuous flow proof of concept can further stimulate the use of continuous flow for polypeptide synthesis potentially streamlining N ‐carboxyanhydride ring opening polymerization.